(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the topical issues of teaching Russian language at non-linguistic faculties of higher education institutions. The article considers communicative competence as a broad concept, including not only structural features of language (Russian language), but also its social, pragmatic and contextual features. The scientific and methodological foundations for the formation of communicative competence in teaching Russian to students of non-language universities are highlighted.